Dampak kualitas produk dan promosi terhadap keputusan pembelian produk avoskin di Kota Bandar Lampung - Patmarina, Hepiana; Amelia, Tiara (Nur Science Institute, 2025)
The research objective is determining how promotion and product quality impact consumer buying decisions. Where there are fluctuations in sales data, which in this study reflect instability in consumer purchasing decisions, one of the common problems today is that some consumers judge the quality of a product by referring to the price given. The descriptive quantitative method used in this study aims to analyse Avoskin Skincare consumer behaviour. The research sample included 97 students in Bandar Lampung who had used Avoskin products, selected using the Lemeshow formula. Data was collected through a survey distributed through Google Forms. The collected data were then processed and analysed. From the research that has been carried out, it is found that product quality has a positive and significant influence on purchasing decisions for Avoskin products, as well as promotions that have a significant impact. This research shows that product quality is the main factor influencing purchasing decisions, although promotions still play an important role in shaping consumer decisions.Keywords: Purchase Decision, Product Quality, Promotion.